Research priorities and trends in pulmonary tuberculosis in Latin America: A bibliometric analysis - Morán-Mariños, Cristian (2024)
Tuberculosis (TB) poses a significant global public health challenge, particularly in developing countries. Over the years, scientific research has played a pivotal role in addressing this disease. In this study, we aimed to analyze and outline the trends in scientific output on TB and identify research priorities in Latin America (LA) from 1990 to 2021. Scientific production was analyzed, and the number of publications, financing sources, and journal characteristics were evaluated. Collaboration networks and keywords were visualized using mapping analysis with VOSviewer software. Research themes were prioritized by country based on co-occurrence frequency. In total, 4399 documents were identified, a significant trend was evident in the number of publications per year (R2 = 0.981), and research substantially contributed to the reduction of TB-related mortality (R2 = −0.876). Most publications were original articles (83.8 %). The International Journal of Tuberculosis and Lung Disease had the highest publication and citation rates per document. International collaboration was predominantly with the United States, France, and Canada. Brazil, Argentina, and Mexico had the highest number of publications and external collaborations. In LA, interest in researching studies related to treatment and diagnosis (32.5 %) was notably high, followed by epidemiology and screening (26.9 %). Among the 20 countries in LA, research priorities varied, with the highest emphasis on HIV/AIDS (14/20), epidemiology (9/20), anti-TB agents (6/20), and mortality (5/20). TB resistance was only considered a research priority in Brazil, Peru, and Haiti. Therefore, LA experienced significant growth in its scientific output, playing a crucial role in TB control. Strategic adaptation to the region's specific challenges was observed, particularly in HIV/AIDS coinfection, epidemiological studies, and drug resistance. This progress was achieved by outstanding international scientific collaboration. This holistic approach emphasizes the importance of research in the fight against TB in LA.